1995
DOI: 10.4141/cjas95-091
|View full text |Cite
|
Sign up to set email alerts
|

The effect of formic acid and buffering capacity on the ileal digestibilities of amino acids and bacterial populations and metabolites in the small intestine of weanling pigs fed semipurified fish meal diets

Abstract: R. 1995. The effect of formic acid and buffering capacity on the ileal digestibilities of amino acids and bacterial populations and metabolites in the small intestine of weanling pigs fld semipurified fish meal diets. Can. J. Anim. Sci. 75: 615423. An experiment was carried out to examine the effects of supplementa:tion of formic acid to semipurified diets containing fish meal for weanling pigs with low and high buffering capacity on nutrient digestion and bacterial populations and metabolites in the small int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
9
0
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 35 publications
(31 reference statements)
6
9
0
3
Order By: Relevance
“…The SID of indispensable AA in FM1 in the present study are in good agreement with SID calculated from the corresponding AID obtained in the study by Gabert et al (1995). In contrast, SID of indispensable AA in FM2 e were up to 11 percentage units smaller compared with the corresponding SID calculated from AID of indispensable AA (Gabert et al, 1995). The transformation of AID of indispensable AA determined in the study by Kim and Easter (2001) into the corresponding SID resulted in 21 and 17 percentage units smaller SID for FM1 and FM2 e , respectively, compared with the results of the present study.…”
Section: Amino Acid Digestibility In Pigletssupporting
confidence: 80%
See 2 more Smart Citations
“…The SID of indispensable AA in FM1 in the present study are in good agreement with SID calculated from the corresponding AID obtained in the study by Gabert et al (1995). In contrast, SID of indispensable AA in FM2 e were up to 11 percentage units smaller compared with the corresponding SID calculated from AID of indispensable AA (Gabert et al, 1995). The transformation of AID of indispensable AA determined in the study by Kim and Easter (2001) into the corresponding SID resulted in 21 and 17 percentage units smaller SID for FM1 and FM2 e , respectively, compared with the results of the present study.…”
Section: Amino Acid Digestibility In Pigletssupporting
confidence: 80%
“…GfE, 2008;Rademacher et al, 2009), these AID were transformed into the corresponding SID according to the principles as described herein (equation (2)). The SID of indispensable AA in FM1 in the present study are in good agreement with SID calculated from the corresponding AID obtained in the study by Gabert et al (1995). In contrast, SID of indispensable AA in FM2 e were up to 11 percentage units smaller compared with the corresponding SID calculated from AID of indispensable AA (Gabert et al, 1995).…”
Section: Amino Acid Digestibility In Pigletssupporting
confidence: 78%
See 1 more Smart Citation
“…Differences in the diet composition, buffering capacity and farming practices make it difficult to compare results from different studies. However, in general, significant effects on performance and intestinal microbiota were observed in trials with higher than 0.5% inclusion level of FA (Bolduan et al, 1988;Partanen and Mroz, 1999;Canibe et al, 2005;Franco et al, 2005), whereas studies using less than 0.5% FA did not report significant effects (Gabert et al, 1995;Knarreborg et al, 2002). This, together with the observations made in the present investigation, strongly suggest that it is the inhibitory, rather than stimulatory, effect of FA that improves the animal performance.…”
Section: Discussionsupporting
confidence: 55%
“…Partanen et al (2007) noted that addition of 0.84% organic acid mixture (formic acid, sorbate and benzoate) to pig diets had improved the apparent ileal digestibility of almost amino acids. In contrast, Gabert et al (1995) did not found any effect of formic acid supplementation on apparent ileal digestibilities of amino acids for early-weaned pigs.…”
Section: โ…ณ Discussionmentioning
confidence: 56%